(untitled) (IUS LAW Journal, 2025)
Arguably the adoption of the Convention on the Rights of Persons with Disabilities represents an important progressive development in the protection framework accorded to physically challenged persons under International Humanitarian Law. The objective of this paper is to examine the extent of protection accorded to physically challenged persons from harm in situations of risk consistent with International Humanitarian Law. The paper argued that examining the applicable legal and policy framework aimed at protecting the rights of physically challenged persons under international humanitarian law is not only a programmatic goal to be attained in the long term, but rather an immediate task on Countries to adopt measures in this without delay. This is against the backdrop driven by the desire to create stability between the rules of International Humanitarian Law(IHL) and the Convention on the Rights of Persons with Disabilities(CRPD) both in times of peace and armed conflict. It is therefore important to reiterate the fact that if the future of physically challenged persons must be guaranteed, the need to take cognizance of their peculiarities must not be overlooked. It is therefore advanced that the continued neglect of peculiarities of physically challenged persons both under the Convention and International Humanitarian Law portends a clog in the general protection against the effects of armed conflict or humanitarian emergencies. This paper adopts an analytical and qualitative approach and built its argument on existing literature which is achieved by a synthesis of ideas. Nevertheless, this article provides some recommendations that will guarantee special protection to physically challenged persons derivable from the principle of humanity.